Comparison of Children’s Medical and Dental Insurance Coverage by Sociodemographic Characteristics, United States, 1995 - Clemencia M. Vargas, DDS, PhD; Robert E. Isman, DDS, MPH; James J. Crall, DDS, ScD (Blackwell Synergy, 2002)
Insurance coverage can reduce financial barriers that constitute a significant deterrent to obtaining medical and dental care, especially for children who reside in low-income households. We present baseline information on the codistribution of medical and dental coverage among US children according to sociodemographic characteristics before the enactment of the State Children’s Health Insurance Program (SCHIP).